Entrepreneurial Environment in the Current Financial Politics of Kazakhstan - UAKHITZHANOVA, Anargul; SHOKHAN, Roza; OMAROVA, Ainura; DAULETOVA, Aziza; KAMENOVA, Mazken; AIMURZINA, Baglan (Journal of Advanced Research in Law and Economics, 2017)
One of the difficult economic problems in Kazakhstan's modern financial policy is to maintain the pace of economic development in the face of global financial instability. The course on economic growth presupposes the intensification of the development of entrepreneurship and the enhancement of its role in the national economy. Entrepreneurship as a special way of economic activity is called upon to stimulate the diversity of forms of management, strengthening of intraeconomic development, expansion of employment of the population and realization of competitive advantages of Kazakhstan in the international division of labor. The entrepreneurial environment and the real sector of the economy were most affected by the global crisis. Despite this, the domestic economy continues to show positive dynamics in this difficult time. Reforms aimed at improving the key characteristics of the business environment, diversification of the economy and more active coverage of investment opportunities in the country are being carried out.